2017
DOI: 10.1093/ckj/sfx086
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course after parathyroidectomy in adults with end-stage renal disease on maintenance dialysis

Abstract: BackgroundParathyroidectomy (PTX) is done in cases of secondary hyperparathyroidism from chronic kidney disease to improve renal osteodystrophy. Despite this widespread practice, clinical outcomes regarding the benefits of this procedure are still lacking. Most studies in the literature have opted to report the laboratory outcome instead. Our study aimed to evaluate the postoperative clinical course for patients who had undergone total PTX without autoimplantation.Methods and resultsAll patients who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…Risk factors proposed to date include a lower preoperative corrected serum calcium concentration, radiologic evidence of osteitis fibrosa cystica, a higher bone-specific ALP concentration, and a greater weight of the resected parathyroid glands. 16 , 19 , 48 50 Our multiple logistic regression analysis showed that the preoperative ALP concentration was an independent predictor of hypocalcemia: a higher preoperative ALP concentration was associated with a higher incidence of postoperative hypocalcemia. In agreement with our findings, patients with a high preoperative ALP concentration are reportedly more likely to develop postoperative hypocalcemia and even HBS.…”
Section: Discussionmentioning
confidence: 77%
“…Risk factors proposed to date include a lower preoperative corrected serum calcium concentration, radiologic evidence of osteitis fibrosa cystica, a higher bone-specific ALP concentration, and a greater weight of the resected parathyroid glands. 16 , 19 , 48 50 Our multiple logistic regression analysis showed that the preoperative ALP concentration was an independent predictor of hypocalcemia: a higher preoperative ALP concentration was associated with a higher incidence of postoperative hypocalcemia. In agreement with our findings, patients with a high preoperative ALP concentration are reportedly more likely to develop postoperative hypocalcemia and even HBS.…”
Section: Discussionmentioning
confidence: 77%
“…However, these treatments do not always provide adequate control of SHPT, particularly among patients with severe parathyroid hyperplasia [8,9]. Successful parathyroidectomy can drastically decrease PTH levels, improve control of serum calcium and phosphorus levels, ameliorate symptoms related to SHPT, and reduce cardiovascular events and overall mortality in dialysis patients [10][11][12]. PTX is, thus, currently recommended in dialysis patients with severe SHPT who fail to respond to medical treatment [13].…”
Section: Introductionmentioning
confidence: 99%
“…The surgical management of rHPT involves standard bilateral exploration with or without bilateral cervical thymectomy. Since the first parathyroidectomy for secondary hyperparathyroidism was performed by Fergusson in 1967, several surgical approaches have been reported, namely total parathyroidectomy alone, total parathyroidectomy with autotransplantation, subtotal parathyroidectomy, and resection of only the enlarged parathyroid glands [11]. However, the optimal timing, extent, and type of surgery for rHPT remain a constant matter of debate.…”
Section: Discussionmentioning
confidence: 99%